Reaksi Likenoid Sebagai Akibat Penggunaan Obat Antihipertensi pada Rongga Mulut - Anindita Laksitasari; Ridhofar Akbar Khusnul Abdillah; Rinawati Satrio; Maulina Triani; Aris Aji Kurniawan; Ryana Budi Purnama; Rakhmawati Rakhmawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
A lichenoid reaction is commonly finding in the oral cavity. A lichenoid reaction may be caused by systemic drugs. Among the drugs are antihypertensive drugs. The aim of this study is to know the treatment of patient with oral lichenoid reaction. Male patient came into RSGM Unsoed complaining of white patches on the right gums near 3rd molar three months ago. The white patches were painless and approximately 0.5 in diameter. Anamnesis was presenting patients is conducted and has been shown that they take 6 years of antihypertensive drugs and are prescribed by their own physician in the city of Semarang. The patient was then instructed on how to keep the oral hygiene and be evaluated two weeks later. Patients then having a normal tension and were off drugs for the following 2 weeks and got a slightly reduced lesion when it was carried out by control. Treatment of a lichenoid reaction can be done with communication, information, and education about his condition to the patient first. Another conservative treatment of topical corticosteroids is recommended when symptomatic symptoms occur. Treatment of patients with an asymptomatic reaction can be done with communication, information, and education to the patient and drug substitution if perceived as needed. Another treatment that can be taken is by using the topical corticosteroid if the lesion is symptomatic.